Is it feasible to think about an internal energy market in MERCOSUR? : A first approach - Lara, Ignacio Fernando (2006)
Given the relevance of energy for MERCOSUR’ economies and given that energy markets’ interdependence is continuously increasing in the subregion, this paper will inquire about the feasibility and prospects of an internal energy market in the near future. The paper will take into consideration not only MERCOSUR Member States, but also some of its Associated States. After a brief introduction about hydrocarbons and electricity markets’ current situation in the subregion, the analysis will be focused on energy markets reform in the diverse subsectors carried out by the respective na-tional governments from the ‘90s up till now. In a successive step, it will be the turn of regional energy market interconnections. Related to this very last issue, the paper will deal with energy interdependence’s current situation in the above mentioned markets and the feasibility of its deepening through an institutionalized coordination at the MERCOSUR level. Finally, some conclusions about the analysis carried out will be given as well as some forecasts about the practical possibility of an internal market in some of the sub sectors studied.